2013
DOI: 10.1242/dev.087130
|View full text |Cite
|
Sign up to set email alerts
|

Lethal giant larvae 2 regulates development of the ciliated organ Kupffer’s vesicle

Abstract: SUMMARYMotile cilia perform crucial functions during embryonic development and throughout adult life. Development of organs containing motile cilia involves regulation of cilia formation (ciliogenesis) and formation of a luminal space (lumenogenesis) in which cilia generate fluid flows. Control of ciliogenesis and lumenogenesis is not yet fully understood, and it remains unclear whether these processes are coupled. In the zebrafish embryo, lethal giant larvae 2 (lgl2) is expressed prominently in ciliated organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 67 publications
7
41
0
Order By: Relevance
“…These data suggest that KV morphogenesis can be uncoupled from KV ciliogenesis. This is consistent with published reports in which reduced KV lumen can have normal cilia length (Tay et al, 2013). Moreover, KV formation is a multistep process requiring proper migration and adhesion of precursor cells, lumenogenesis and ciliogenesis (Oteiza et al, 2010; Schneider et al, 2008; Tayeh et al, 2008; Yen et al, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…These data suggest that KV morphogenesis can be uncoupled from KV ciliogenesis. This is consistent with published reports in which reduced KV lumen can have normal cilia length (Tay et al, 2013). Moreover, KV formation is a multistep process requiring proper migration and adhesion of precursor cells, lumenogenesis and ciliogenesis (Oteiza et al, 2010; Schneider et al, 2008; Tayeh et al, 2008; Yen et al, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…Thus, we found that atp1b1a and lgl2 not only genetically interact during epidermal cell polarity and malignancy but also during edema formation and Na/K-ATPase a-subunit localization ( Figure 7-figure supplement 1), in line with previous reports of pronephric defects and mild edema formation in lgl2 morphants (Tay et al, 2013). However, atp1b1a and lgl2 mutants also display differences.…”
Section: The Cooperation Between Atp1b1a and Lgl2supporting
confidence: 91%
“…In addition to previously described probes ( cmlc2 , foxa3 and spaw ), pitx2c and elovl6 probes were made from corresponding cDNAs amplified from a zebrafish cDNA library (see primer sequences above) and cloned using a TOPO TA cloning Kit (invitrogen). elovl6 expression was analyzed in cftr pd1048 mutants (Navis et al, 2013) or embryos injected with Lgl2 morpholino (5′-gcccatgacgcctgaacctcttcat-3′) (Tay et al, 2013). gh1 (primers: 5′-atggctagagcattggtgc-3′ and 5′-tacagggtacagttggaatc-3′) and pomca (primers: 5′-atggtgaggggagtgaggatg-3′ and tcact-catccttcctcggttg-3′) cDNA fragments were cloned using a TOPO TA cloning kit with a pCRII-TOPO vector (Invitrogen) and used as templates for antisense probes.…”
Section: Methodsmentioning
confidence: 99%